Comparative Study of Reproductive Behaviors in Two Ethnicities of Fars and Turkmen in North Khorasan, Iran - Zohreh Abasi; Zohreh Keshavarz; Mohammad Jalal Abbasi- Shavazi; Abbas Ebadi; Habibollah Esmaily; Salar Poorbarat (Journal of Midwifery & Reproductive Health, 2022)
Background & aim: Cohesion and sense of ethnicity belonging can be effective in shaping reproductive behaviors. The aim of this study was to compare the reproductive behaviors in two ethnicities of Fars and Turkmen in North Khorasan, Iran.Methods: This cross-sectional study was performed on 406 Fars and Turkmen women using a self-structured reproductive behavior questionnaire between April and September 2017. Content validity and reliability of the tool was confirmed with Cronbach's alpha of 0.75. Data was collected on a self-report basis and analyzed using SPSS software (version 21) and descriptive and analytical indices.Results: Reproductive behaviors were significantly different between the two groups in terms of number of children (P=0.001), the timing of the first childbirth (P=0.043), interval between the first and second pregnancy (P=0.002), desire to re-childbearing (P=0.002), number of desired children (P=0.025), current method of contraception and decision to continue or terminate unwanted pregnancies (P=0.074). General linear test showed that with the introduction of demographic variables to measure the effect of the number of children in the analysis, the effect of ethnicity on the number of children was removed, but the variables of maternal age (P=0.001), husband's age (P=0.001), education of woman and husband (P=0.001) and the woman's job (P=0.001) remained as effective variables on the number of children.Conclusion: Today, the value of childbearing has changed more than other family values. In order to achieve the targets of population policies, population policy-making must be based on economic, social, cultural and demographic realities of the societies.